Crosstalk of Exosomal Non-Coding RNAs in The Tumor Microenvironment: Novel Frontiers - Jia, Zimo; Jia, Jinlin; Yao, Lihui; Li, Zhihan (Frontiers in Immunology, 2022)
The tumor microenvironment (TME) is defined as a complex and dynamic tissue entity composed of endothelial, stromal, immune cells, and the blood system. The homeostasis and evolution of the TME are governed by intimate interactions among cellular compartments. The malignant behavior of cancer cells, such as infiltrating growth, proliferation, invasion, and metastasis, is predominantly dependent on the bidirectional communication between tumor cells and the TME. And such dialogue mainly involves the transfer of multifunctional regulatory molecules from tumor cells and/or stromal cells within the TME. Interestingly, increasing evidence has confirmed that exosomes carrying regulatory molecules, proteins, and nucleic acids act as an active link in cellular crosstalk in the TME. Notably, extensive studies have identified non-coding RNAs (ncRNAs), including long non-coding RNAs (lncRNAs), microRNAs (miRNAs), and circular RNAs (circRNAs), that could be encapsulated by exosomes, which regulate the coordinated function within the TME and thus participate in cancer development and progression. In this review, we summarize recent literature around the topic of the functions and mechanisms of exosomal ncRNAs in the TME and highlight their clinical significance.